itu Experimental Analysis of the Effects of Intake Manifold Length and Angle Variations on Torque and Power in 110 cc Fuel Injected Motorcycles - Baimy Alexander; Nanang Ruhyat (G-Tech: Jurnal Teknologi Terapan, 2025)
The performance of small displacement motorcycle engines is significantly influenced by the design of the intake manifold, particularly its geometric characteristics such as length and bend angle. This study examines the effects of intake manifold geometry variations on the performance of a 110 cc fuel injected motorcycle engine. Nine configurations were tested, combining three intake lengths (3 cm, 9 cm, and 12 cm) and three bend angles (0°, 20°, and 40°). A dynamometer was used to measure engine output in terms of torque and power. Results indicate that manifold geometry strongly affects engine performance. The best torque value, 23.40 Nm, was achieved with the 12 cm and 20° configuration, while the highest power output of 9.0 HP came from the 12 cm and 40° configuration. ANOVA confirmed statistically significant effects of both variables (p < 0.05). Unlike previous studies that typically isolate one geometric factor, this research fills a gap by evaluating length and angle together. These findings provide practical insights for optimizing intake manifold design in small fuel injected engines, improving both power and efficiency.